Phenotypical and functional characteristics of in vitro expanded bone marrow mesenchymal stem cells from patients with systemic sclerosis. Issue 4 (25th May 2007) - Larghero, J; Farge, D; Braccini, A; Lecourt, S; Scherberich, A; Foïs, E; Verrecchia, F; Daikeler, T; Gluckman, E; Tyndall, A; Bocelli-Tyndall, C
Abstract : Background: Mesenchymal stem cells (MSCs) have a potential immunomodulatory role in autoimmune disease; however, the qualitative properties and haematopoietic support capacity of MSCs derived from patients with autoimmune disease is unclear. Objectives: To further characterise phenotypically and functionally bone marrow (BM)-derived MSCs from patients with systemic sclerosis (SSc). Methods: Key parameters of BM-derived MSC function and phenotype were assessed in 12 patients with SSc and compared with 13 healthy normal controls. The parameters included the ability to: form colony-forming unit fibroblasts (CFU-F), differentiate along the adipogenic and osteogenic lineages, express cell surface antigens defining the MSCs population, support normal haematopoiesis and suppress in vitro lymphocyte proliferation induced by either anti-CD3∊ plus anti-CD28 monoclonal antibodies or the mixed lymphocyte reaction. Results: SSc MSCs were shown to have a similar characteristic phenotype, capacities to form CFU-F and to differentiate along adipogenic and osteogenic lineages as those of healthy donor MSCs. The ability of SSc MSCs to support long-term haematopoiesis was also identical to that of controls. Both healthy donor and SSc BM MSCs reduced the proliferation of autologous and allogeneic peripheral blood mononuclear cells in a cell number dependent fashion. Conclusions: These results show that BM-derived MSCs from patients with SSc under the described culture conditions exhibit the same phenotypic, proliferative, differentiation potential and immunosuppressive properties as their healthy counterparts and could therefore be considered in an autologous setting. Further studies are needed to ensure the quality and safety of large-scale expansion of patient MSCs prior to their potential use in clinical trials.